2010
DOI: 10.1590/s0066-782x2010000500018
|View full text |Cite
|
Sign up to set email alerts
|

Desbalanço redox: NADPH oxidase como um alvo terapêutico no manejo cardiovascular

Abstract: Multiple enzyme systems produce RONS and their derivatives in the vascular system, including cyclo-oxigenase, lipoxigenase, P450 cytochrome, xanthine oxidase (XO), myeloperoxidase (MPO), nitric oxide synthase (NOS) and NADPH oxidase -this latter one of the most important sources of this substance, both in endothelial cells as in smooth muscle cells .Since the findings of Baehner et al 23 40 years ago -which allowed the discovery of NADPH oxidase 24 -several studies addressed the relation between said enzyme c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
0
10
0
3
Order By: Relevance
“…The NADPH oxidase 4 (NOX4) protein is located intracellularly in the perinucleus and is a source of ROS 12,13 . This protein has a high expression level in cardiac tissue, although the degree of the difference in expression between the vessels and the myocardium is unclear.…”
Section: Nadph Oxidase 4 (Nox4) Genementioning
confidence: 99%
See 1 more Smart Citation
“…The NADPH oxidase 4 (NOX4) protein is located intracellularly in the perinucleus and is a source of ROS 12,13 . This protein has a high expression level in cardiac tissue, although the degree of the difference in expression between the vessels and the myocardium is unclear.…”
Section: Nadph Oxidase 4 (Nox4) Genementioning
confidence: 99%
“…This protein has a high expression level in cardiac tissue, although the degree of the difference in expression between the vessels and the myocardium is unclear. NOX4 presents a differentiated pattern of ROS production following binding of NADPH to its terminal carbon, which facilitates electron transfer, and thereafter via binding of the flavin adenine dinucleotide (FAD) to two heme residues and then to molecular oxygen; this process predominately acts as a source of hydrogen peroxide (H 2 O 2 ) and, to a lesser extent, as a source of superoxide anion (O 2 -) 13,14 . ROS production may increase through modulators of its expression, such as transforming growth factor β, angiotensin II, tumor necrosis factor alpha (TNF-α), and shear stress.…”
Section: Nadph Oxidase 4 (Nox4) Genementioning
confidence: 99%
“…The O 2 •− ion radical reduces the vasodilator properties of NO (nitric oxide), which reacts with high affinity to yield peroxynitrite (ONOO •− ) as a product [18]. Therefore it has been suggested that NOX2 may be an important therapeutic target for the treatment of hypertension [19]. For this purpose, several strategies have been proposed to inhibit NOX2 catalytic activity [20].…”
Section: Introductionmentioning
confidence: 99%
“…As espécies reativas do oxigênio (EROs) incluem os compostos químicos radicalares ou não, formados durante a ativação ou redução do oxigênio molecular. As espécies reativas do oxigênio apresentam papel fundamental em diversas funções fisiológicas, incluindo a Entre os componentes do sistema não enzimático atuam as vitaminas A, C e E (retinol, ascorbato e tocoferol, respectivamente), carotenoides e quelantes de metais(AUGUSTO, 2006;RABÊLO et al, 2010;RIBEIRO et al, 2005).Quanto às fontes de espécies reativas do oxigênio, a mitocôndria é o principal local de produção. Grande parte da energia produzida no organismo é gerada por meio de fosforilação oxidativa, correspondente a cinco complexos enzimáticos: os complexos de I a IV (cadeia de transporte de elétrons), que estão envolvidos no transporte de elétrons através de uma série de proteínas via reações de redução/oxidação, tendo como destino final uma molécula de oxigênio.…”
unclassified
“…Em circunstâncias normais, o oxigênio é, então, convertido em água no complexo IV, e a energia é estocada e usada para a produção de ATP no complexo V. Porém, durante esse processo, cerca de 2 a 5% do oxigênio consumido pela mitocôndria no complexo IV é convertido em uma das várias espécies reativas do oxigênio. A produção de EROs e seus derivados ocorre não só pela cadeia transportadora de elétrons na mitocôndria, mas também por múltiplos sistemas enzimáticos, incluindo ciclooxigenase, lipoxigenase, citocromo P-450, xantina oxidase (XO), mieloperoxidase (MPO), óxido nítrico sintase (NOS) e NADPH oxidase, sendo este último complexo de destaque na formação de EROs, por ser responsável, no Diabetes mellitus, pela principal geração de ânion superóxido(RABÊLO et al, 2010;RIBEIRO et al, 2005). A separação destes dois grupos de componentes em compartimentos distintos garante a regulação do complexo enzimático, e a ativação da enzima se dá pela fosforilação da proteína citoplasmática p47phox, levando todo o complexo citoplasmático a migrar para a membrana e se associar ao citocromo b558.…”
unclassified